An Investment-based Approach to Prosopis Agroforestry in Arid Lands - Felker, Peter (Annals of Arid Zone, 2016)
This paper suggests that many of the social goals of agroforestry in arid lands, i.e.. soil improvement, provision of firewood and income generation, etc., can be accomplished with Prosopis plantations used to produce lumber for fine furniture and flooring. Prosopis lumber compares favorably in color, hardness and shrinkage values to the world’s finest timbers that also belong to the legume family such as padauk (Pteroc.arpus soyauxii), purpleheart (Peltogyne spp.), cocobolo (Dalbergia retusa), Indian rosewood (Dalbergia latifolia), and Brazilian cherry (Hymenaea courbaril). Data from various field trials was combined to produce the scenario of a Prosopis alba plantation on a 10 x 10 m spacing that was annually intercropped. These trees were predicted to achieve 38 cm in diameter in 30 years with a saWn lumber volume of 15.9 m-1 ha-1 worth 856 m-3. After the cost of sawing the trees into lumber ( 107 m-3) and the total plantation costs of 2135 over the 30 years was deducted, the net profit was predicted to be 9,774 ha-1 and the internal rate of return was calculated to be 9.3% using an interest rate of 8%. No value was ascribed to the high sugar content in the. pods, of value to both humans or livestock, to soil improvement from N fixation or to provision of firewood from prunings. Thus, the 9.3% internal rate of return should be considered a minimum value. Due to the long term nature of the investment, plantations for fine lumber may be outside the financial capabilities of rural poor. As a result it may be necessary to attract investors from large investment firms that have a portion of their funds in long term investments.